Rethinking Entrepreneurial in the Digital Economy: Toward A Strategic Framework for Customer Value Creation - Margono, Hery (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2026)
The rapid development of digital technology has significantly transformed the structure of business environments and intensified competition across various industries. The expansion of digital platforms has created new forms of market interaction that allow organizations and consumers to engage in more dynamic and continuous exchanges. At the same time, these changes have reshaped consumer behavior, particularly in how individuals search for information, interact with brands, and evaluate products or services within increasingly connected digital ecosystems. This study aims to examine the evolving dynamics of entrepreneurial marketing in the digital economy and to explore how strategic marketing approaches can strengthen customer value creation in rapidly changing digital markets. The study employs a qualitative approach by analyzing relevant academic literature, previous research findings, and scholarly publications related to entrepreneurial marketing, digital business environments, and customer value development. The findings indicate that the expansion of digital ecosystems has intensified market competition while simultaneously requiring organizations to adopt more adaptive and flexible marketing strategies. Organizations are increasingly required to strengthen interactive communication, integrate digital marketing activities, and build long-term relationships with customers to remain competitive in complex digital markets. Ultimately, reinforcing customer value orientation through improved customer experience and sustained engagement plays a critical role in strengthening the competitive position of organizations operating within the digital economy.